A DFT study of structure and stability of pleated and rippled cross‐β sheets with hydrophobic sidechains. Issue 1 (1st August 2020) - Raskatov, Jevgenij A.
Abstract: The rippled cross‐β sheet, a topography, in which mirror‐image peptides are arranged with alternating chirality into a periodic two‐dimensional network, is burgeoning as a new design principle for materials and biomedical applications. Experiments by the Schneider, Nilsson, and Raskatov labs have independently shown diverse racemic mixtures of aggregation‐prone peptide of different sizes to favor the rippled over the pleated topography. Yet, systematic ab initio studies are lacking, and the field is yet to develop rules that would enable the design of new rippled cross‐β frameworks from first principles. Here, DFT calculations were performed on a set of model systems, designed to begin understanding the impact that bulky, hydrophobic sidechains have upon the formation of pleated and rippled cross‐β frameworks. It is hoped that this study will help stimulate the development of a predictive, general framework to enable rational design of rippled cross‐β sheets in the future. Abstract :